2020
DOI: 10.1016/j.dib.2020.106044
|View full text |Cite
|
Sign up to set email alerts
|

Testing the stability of ‘Default’ motor and auditory-perceptual rhythms–A replication failure dataset

Abstract: Several studies have found that the motor rhythms that individuals produce spontaneously, for example during finger tapping, clapping or walking, are also rated perceptually as ‘very comfortable’ to listen to. This motivated proposal of the Preferred Period Hypothesis , suggesting that individuals have a characteristic preferred rhythm, that generalizes across perception and production. However, some of the experimental procedures used previously raise two methodological conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…These measures capture complementary aspects of tapping accuracy, as described in our previous work (Kliger Amrani and Zion Golumbic 2020b, 2020a) (Figure 2).…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…These measures capture complementary aspects of tapping accuracy, as described in our previous work (Kliger Amrani and Zion Golumbic 2020b, 2020a) (Figure 2).…”
Section: Methodsmentioning
confidence: 92%
“…Previous studies have found that there is a relatively narrow range of rates for which memory-paced tapping is optimal, roughly around ~ 0.6 sec SOA (1.6 Hz). This range corresponds to the rates of spontaneous motor rhythms and perceptual auditory preferences (McAuley et al 2006; McAuley 2010; Roerdink et al 2011; Large and Gray 2015a; Scheurich et al 2018; Zamm et al 2018; Kliger Amrani and Zion Golumbic 2020b, 2020a), leading to the suggestion that they reflect physiological rhythmic-defaults of the auditory and/or motor systems. Given these presumed built-in default rhythmic preferences, here we further tested whether the potential effect of motor engagement manifests similarly across a broad range of rates (from sub-second to supra-second) or whether it interacts with presumed default rhythmic preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have proposed methodological re nements in the measurement of SMT and PPT, leading to a more cautious and conservative interpretation of a preferred period 15,16 . Firstly, when the inter-stimulus interval (ISI) of isochronous sequences presented during PPT measurement are not selected by a participant SMT, no correlation between motor and perceptual rhythmic preferences emerges 15 . According to these researchers, selecting ISI of isochronous sequences in a PPT task based on participants' SMT might introduce a bias toward the central rhythm used.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the above-described confound between endogenously periodic signals and the passive tracking of exogenous periodicities in sensory inputs, we additionally analysed MEG signals recorded while participants engaged in spontaneous overt or covert rhythmic behaviours. The frequency of such behaviours has been argued to reflect a stable internal prior (Jacoby & McDermott, 2017; but see Kliger Amrani & Zion Golumbic, 2020; McPherson et al, 2018; Peper et al, 1995; Zalta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%